2021
DOI: 10.1002/ejoc.202100027
|View full text |Cite
|
Sign up to set email alerts
|

A Conformer‐Dependent, Quantitative Quadrant Model

Abstract: This study reports the development and application of a conformer‐dependent quantitative quadrant descriptor for generating models that relate catalyst performance to catalyst structure in enantioselective transformations. The generality of these descriptors is demonstrated by using them for three different reactions: (1) copper‐catalyzed, enantioselective cyclopropanation of alkenes, (2) rhodium‐catalyzed enantioselective hydrogenation of α‐substituted N‐acyl‐enamides, and (3) enantioselective addition of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Octant models (or quadrants of a half-sphere) have been also used recently by the Denmark group in the analysis of asymmetric cyclopropanation, hydrogenation, and thiol addition . Differently, some of us very recently showed that quadrants of the full sphere can also be used for quantitative prediction of isotactic polypropylene (iPP) enantioselectivity ( R 2 between experimental and fitted data 0.92) of rigid C 2 -symmetric indenyl-based ansa -zirconocenes ,,, , even allowing moderate extrapolation .…”
Section: Introductionmentioning
confidence: 99%
“…Octant models (or quadrants of a half-sphere) have been also used recently by the Denmark group in the analysis of asymmetric cyclopropanation, hydrogenation, and thiol addition . Differently, some of us very recently showed that quadrants of the full sphere can also be used for quantitative prediction of isotactic polypropylene (iPP) enantioselectivity ( R 2 between experimental and fitted data 0.92) of rigid C 2 -symmetric indenyl-based ansa -zirconocenes ,,, , even allowing moderate extrapolation .…”
Section: Introductionmentioning
confidence: 99%
“…The descriptors used include conformer-dependent quantitative quadrant descriptors, [12] Sterimol parameters, [13,14] IR vibration, [13] NBO charges, [13,14] Balaban-type index, [14] average steric occupancy descriptors, [15] and conformer-dependent descriptors. [3] These models dealt with 30, [12] 38, [13] 367, [14] and 1075 [3,15] enantioselectivities ΔΔG in Minisci reactions of diazines, [13] nucleophilic addition reactions to imines, [14] and thiols addition to imines. [3,12,15] Most of the QSSR models stated above were based on small data set, and only the linear regression technique was adopted to develop models.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers focused on QSSR models for enantioselectivities ΔΔG in asymmetric reactions with chiral phosphoric acids as catalysts. The descriptors used include conformer-dependent quantitative quadrant descriptors, [12] Sterimol parameters, [13,14] IR vibration, [13] NBO charges, [13,14] Balaban-type index, [14] average steric occupancy descriptors, [15] and conformer-dependent descriptors. [3] These models dealt with 30, [12] 38, [13] 367, [14] and 1075 [3,15] enantioselectivities ΔΔG in Minisci reactions of diazines, [13] nucleophilic addition reactions to imines, [14] and thiols addition to imines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations